Staff experience of a new approach to family safeguarding in Oxfordshire Children's Social Care Services - Buivydaite, R; Morgan, M; Irving, D; Carter, J; Farncombe, H; Vincent, C (Wiley, 2023)
This paper presents the findings from a qualitative study that sought to understand the experiences of frontline staff working in Oxfordshire County Council (OCC) Children's Social Care Services and their views on a new family safeguarding model (Family Solutions Plus). Focus group interviews were conducted with 20 frontline staff and managers in different teams across OCC Children's Social Care Services using video conferencing software. Thematic analysis identified three overarching themes: Preparation for the implementation of Family Solutions Plus, staff views on the implemented model, and challenges to its implementation. Staff voiced strong support for the new model, which places a much greater emphasis than previous practice on supporting the whole family, developing parenting skills and keeping children safe with their families. The challenges associated with the transition to a new model were considerable in the short term, partly due to the COVID-19 pandemic, but there was optimism that the new model could be sustained and stabilized over time.